Internet Addiction and Its Impact on Emotional Intelligence Among Adolescents - Sari, Anggi Maulida; Tasnimin, Tasnimin (Poltekita: Jurnal Ilmu Kesehatan, 2024)
This study aimed to investigate the relationship between internet addiction and emotional quotient (EQ) among adolescents at SMPN 1 Meulaboh. A cross-sectional quantitative approach was employed, utilizing structured interviews with carefully designed questionnaires. The target population consisted of 350 students, and a simple random sampling technique was used to ensure representativeness and reduce bias. Data were analyzed using Pearson Correlation to determine the relationship between the two research variables. The results revealed a significant relationship between internet addiction and EQ (p < 0.05), with a weak positive correlation (r = 0.280). This indicates that changes in internet addiction levels may influence EQ among the adolescents. The findings highlight the importance of understanding the factors triggering high internet usage intensity in adolescents and the need for a holistic approach in managing their technology-related behavior. Awareness of the potential negative impacts on EQ can inform preventive and intervention efforts. Future research should expand the studied variables, including psychological, environmental, and social factors affecting adolescents' EQ, and consider qualitative methods to clarify the results. Developing intervention programs to help adolescents manage their online time wisely and enhance their EQ is also recommended.